Challenges and Prospects for Health Workforce Management - A. V. Starshinin; Yu. V. Burdastova (Здоровье мегаполиса, 2023)
Background. The key to building an effective healthcare system is to provide highquality treatment, take measures for disease prevention, and make medical care more accessible for all population groups. Today, the Russian healthcare system has a lot of serious issues in human resources management that require urgent solutions.Purpose. To identify the specifics of staffing in Moscow healthcare, the motivation of medical personnel working in public medical organizations, and the problems and opportunities for managing human resources.Materials and methods. The research data was collected within a qualitative sociological study conducted by the Research Institute for Healthcare Organization and Medical Management of the Moscow Healthcare Department in 2019. The study method was an expert survey using indepth, structured interviews. 15 expert interviews were devoted to the staffing of Moscow healthcare. The interview participants were the Moscow experts in the secondary professional medical education, the higher professional medical education, or the continuing professional education of medical workers, as well as the chief physicians of Moscow medical organizations.Results. The availability of medical personnel in Moscow is quite high. In comparison with other regions, Moscow has competitive pay, career growth opportunities, and social protection, so the problem is not particularly acute. However, health professionals often move to the private sector due to the high workload of physicians and nurses in public health facilities.